Smiths Falls in the World: A Study of Globalization in a Rural Canadian Town - Jinha, Arif E (Just Labour, 2009)
In early February, 2007, Hershey’s Chocolate Company announced its global supply-chain transformation plan to cut more than 1500 jobs from its Canadian and United States plants. Smiths Falls, the Chocolate Capital of Canada, lost its Hershey factory together with the closure of the Rideau Regional Centre, an institution for people with developmental disabilities. By the end of 2008, this Eastern Ontario town of roughly 9,000 people shed roughly 1700 jobs, constituting almost 40% of its active labour force (Sutton, 2009). Globalization, despite the confusion generated by the word, must be considered a core factor in the economic and social situation. Smiths Falls confronts these lay-offs from a position of economic and social strain already. The paper examines the broader changes in the world occurring through globalization and how the local society of Smiths Falls has adjusted in tandem. Such an analysis has likely been relevant to Smiths Falls since its inception; as a meeting point of transcontinental trade and a centre of manufacturing within an ever-expanding and more complex supply chain.